A novel blanket annealing process to achieve highly transparent and conducting Al doped ZnO thin films: Its mechanism and application in perovskite solar cells. (1st November 2018) - Ghosh, Shuvaraj; Mallick, Arindam; Dou, Benjia; van Hest, Maikel F.A.M.; Garner, Sean M.; Basak, Durga
Graphical abstract: Highlights: A unique Zn blanket annealing process to control compensating defects in AZO thin films. Decrease in compensating defects in AZO due to excess Zn diffusion. As low as 8.8 Ω/sq sheet resistance and 90% visible transmittance of AZO is at par with commercial ITO. Developed film performance as TCO in perovskite solar cells is quite good. Abstract: Achievement of high conductivity by doping an oxide thin film while maintaining its high visible transparency remains a challenge in the field of materials science and technology. Here, we demonstrate a simple and novel technique to control compensating defects in Al doped ZnO (AZO) thin films involving a post-growth annealing process with Zn blanket. We also provide an in-depth understanding of the mechanism of achieving high conductivity. As low as 8.8 Ω/sq sheet resistance (resistivity 3.1 × 10 −4 Ω cm) with 90% visible transmission value and wherefrom a figure of merit (FOM) value of 6.5 × 10 −2 Ω −1 for a RF sputtered 350 nm AZO thin film can be achieved. Such very low sheet resistance has been attributed to a decrease in the number of compensating defects and lesser out diffusion of Zn in AZO. Application of the developed AZO film as conducting substrate has successfully been tested by fabricating perovskite solar cells on flexible Corning® Willow® Glass substrate. The present findings open up the possibility of enough high quality industrial-scale production of transparent conducting oxides (TCOs) bearing crucial significance from the perspective of transparent electrodes for solar cells.